2010
DOI: 10.1007/s11270-010-0675-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Stormwater on Sediment Quality in an Enclosed Bay of the Lule River, Northern Sweden

Abstract: Sediment and porewater samples from an enclosed bay receiving stormwater discharge (Skutviken) near the centre of Luleå, northern Sweden were analysed for major and trace elements and 16 polycyclic aromatic hydrocarbons (PAHs). Among the studied metals Cd, Cu, Pb and Zn were enriched at Skutviken. Also, the PAH content was enriched, in particular for phenantrene, anthracene, fluoranthene and pyrene which are regarded as common constituents in stormwater. The use of trace metal ratios provided indications about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[4][5][6][7] Based on these studies, it can be concluded that most of the stormwater sediments are contaminated by heavy metals, phosphorus, trace organic and hydrocarbon and cannot be disposed of without treatment. [5][6][7][8][9][10] Generally, the current disposal treatment options fall into one of three different types, namely (1) biological; (2) chemical/immobilization; and (3) thermal processes. A wide variety of organics and heavy metals associated with stormwater sediment was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Based on these studies, it can be concluded that most of the stormwater sediments are contaminated by heavy metals, phosphorus, trace organic and hydrocarbon and cannot be disposed of without treatment. [5][6][7][8][9][10] Generally, the current disposal treatment options fall into one of three different types, namely (1) biological; (2) chemical/immobilization; and (3) thermal processes. A wide variety of organics and heavy metals associated with stormwater sediment was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Mayer et al [ 51 ] observed that aqueous PAHs were below instrument detection limits and that 91% of PAHs were particulate-bound. Particle-bound PAHs tend to have high molecular weight [ 4 , 27 , 49 , 64 , 81 ], while low-molecular-weight PAHs predominantly are found in dissolved phases [ 27 ]. This would explain some of the unremarkable PAH concentrations found in filtered SW samples, especially high-TSS August 22 samples, as the bulk of PAHs would remain within the filter sediment.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulated sediment in the ponds has entrained pollutants for typically decades before being removed in a dredging operation. Therefore, sediment in wet ponds usually contains high levels of multiple pollutants [6,7] but also exhibits significant heterogeneity in the types and levels of accumulated pollutants between ponds [8]. Dredging operations move the accumulated sediment from one environment to another.…”
Section: Introductionmentioning
confidence: 99%